How earmarking has become self-perpetuating in United Nations development co-operation - Max-Otto Baumann (Development Policy Review, 2021)
Motivation The share of earmarked funding to the development pillar of the United Nations (UN) has risen to a record level of 79% (2018) of its total revenue/spending. This poses severe implications for the organizational efficiency, aid effectiveness and multilateralism of the UN. Reforms have not been able to stem the trend towards earmarked funding, raising the question of what explains the continued rise of earmarking in the United Nations Development System (UNDS). Purpose This article aims to add a new perspective on earmarking, specifically in the UN. It tries to explain not the root causes of earmarking, but the dynamics of the significant rise over the last decade. The argument is that earmarking has been driven by three vicious circles: by the rational factors associated with a collective action breakdown, a change in norms of appropriateness, and institutional fragmentation. Approach and methods The article draws on funding data from the UN, on 65 interviews with UN staff and donor representatives conducted in the context of a recent research project, and on document analysis. Special attention is given to two donors, Sweden and Germany, dedicated multilateralists that have increased their earmarked resources in recent years. Findings Conventional explanations of earmarking in the UN—dissatisfaction with the performance of UN organizations, the desire for more accountability, policy differences with organizations—cannot fully explain the significant rise in earmarking over the last decade. Empirical evidence supports the hypothesis that the UN system has reached a tipping point, so that earmarking has become self-perpetuating. Policy implications The findings put a question mark after the premises that have so far guided practical efforts by the UN and member states to reduce the share of earmarked funding. They suggest that more fundamental changes to rules and incentives are required to rebalance the UN's funding towards core contributions. Four specific recommendations are derived from the analysis.
Keywords: 300; development; earmarking; UN